Air co-gasification process of LDPE/HDPE waste based on thermodynamic modeling: Hybrid multi-criteria decision-making techniques with sensitivity analysis. (19th January 2023) - Hasanzadeh, Rezgar; Mojaver, Parisa; Khalilarya, Shahram; Azdast, Taher
Abstract: Gasification process is an efficient thermochemical disposal technique and is growing fast in the plastic waste field, nowadays. Co-gasification of low-density and high-density polyethylene waste with different composition ratios was developed in this study and subjected to a hybrid multi-criteria decision-making (MCDM) techniques after validation by comparing with experimental data. A comprehensive parametric study was conducted by considering interaction effects of gasification parameters on the outputs. The MCDM problem involved eleven alternatives and five energy, environmental and economic criteria of gasification performance indicators including hydrogen production, energy efficiency, carbon dioxide emission, heating value of syngas and purchasing cost. The criteria weighting was performed using analytical hierarchy process, Shannon entropy technique and their composite weighting method. TOPSIS and VIKOR techniques were coupled by criteria weighting methods for alternative ranking. L0H100 alternative, i.e. composition of 0 wt% of low-density polyethylene waste and 100 wt% of high-density polyethylene waste, was the best alternative in almost all cases. This alternative had the minimum CO2 emission of 4.98 g/mol, the minimum purchasing cost of 0.96 $/kg and led to the maximum heating value of 126.8 kJ/mol. The findings revealed that VIKOR technique was sensitive to the criteria weights; however, TOPSIS method was independent from the changing the criteria weights. Highlights: Co-gasification of low-density and high-density polyethylene waste was modeled. Co-gasification was subjected to hybrid multi-criteria decision-making techniques. Energy, environmental and economic criteria were considered. Criteria weighting was done by analytical hierarchy process and Shannon entropy. A sensitivity analysis was conducted on criteria weighting.